The Stanford Global Health Media Fellowship: Training the Next Generation of Physician Communicators to Fight Health Misinformation. (23rd June 2022) - Krohn, Kristina M.; Yu, Gina; Lieber, Mark; Barry, Michele
Abstract : Problem: The COVID-19 pandemic and the spread of related health misinformation, especially on social media, have highlighted the need for more health care professionals to produce and share accurate health information to improve health and health literacy. Yet, few programs address this problem by training health care professionals in the art of science writing and medical journalism. Approach: Created in 2011, the Stanford Global Health Media Fellowship aims to train medical students and residents in public communication strategies. Each year, 1 physician-in-training is selected to complete the fellowship, which includes 3 rotations: (1) 1 academic quarter at Stanford's Graduate Program in Journalism, (2) 3 to 5 months with a national news network (previously NBC and ABC, now CNN), and (3) a placement at an international site. During the year-long program, fellows also complete a capstone project tackling a global health equity issue. Outcomes: Since 2011, 10 fellows have completed the program, and they have acquired skills in reporting, writing, multimedia, social media, and medical communications. During the news network rotation, they have completed more than 200 medical news pieces and improved the quality of the health information in a myriad of other pieces. Alumni have continued to write and report on medical stories throughout residency, other fellowships, and as practicing physicians. One alumnus is now a medical news producer at CNN. Next Steps: Expanding high-quality training in medical journalism for physicians through partnerships with journalism schools; communications departments; and local, national, and international journalists can greatly improve physicians' ability to communicate with the public. It also has the potential to greatly improve the health information the public receives. Educators should consider embedding mass health communications training in medical education curricula and increasing opportunities for physicians to engage with diverse public audiences.